Travel and tourism policies and enabling conditions: An analysis of strategies in Mauritius and Egypt - Rasethuntsa, Boitumelo Caroline; Perks, Sandra (Turyzm/Tourism, 2022)
The best travel and tourism policies and enabling conditions play a significant role in promoting tourism competitiveness. Africa’s weak global tourism competitive position emanates from its inability to develop appropriate tourism policies and its failure in providing enabling structures to support competitive tourism among others. The aim of this article is thus to investigate the best travel and tourism practices used by high-ranking African countries (Egypt and Mauritius) in the Travel and Tourism Competitive Index (TTCI) to suggest suitable travel and tourism policies and create enabling conditions to promote tourism elsewhere in Africa. The study analyses secondary data about the best practices applied to prioritise the tourism sector, international openness, price competitiveness and environmental sustainability. It is established that the two selected countries utilise strategies such as the establishment of promotion bodies, diversify their markets, search for investment, pursue the expansion of air transport, practice international openness through embassies and bilateral agreements, and develop and enforce environmental laws. The study identified that collaborative efforts between all tourism stakeholders were an essential component in establishing a healthy tourism industry. This article contributes towards the body of knowledge by highlighting how African countries can model tourism policies and supportive structures to enhance their competitiveness.